A Student-Initiated Course in Socialism - Arnesen, Eric; Ebb, David; Rome, Stephen; Ward, Stephen (Radical Teacher, 2023)
This article, reprinted from Radical Teacher #9 (1978), describes a student-initiated and student-taught course, “Towards a Socialist America,” that was offered at Wesleyan University in the mid-late 1970s.